Fabrication of an electrochemical sensor based on eggshell waste recycling for the voltammetric simultaneous detection of the antibiotics ofloxacin and ciprofloxacin - M. Khodari; H. F. Assaf; Ahmed A. Shamroukh; E. M. Rabie (BMC Chemistry, 2023)
Abstract In this work, an accurate, highly sensitive, and economical electrochemical sensor based on a carbon paste electrode modified by Ca2CuO3 nanostructure (Ca2CuO3 NS) was constructed using Eggshell waste recycling as a cheap source of calcium. The Ca2CuO3 NS was analyzed using FTIR, SEM, and XRD measurements. The synthesized nanomaterials utilized for the first time to enhance the electrocatalytic efficiency of carbon paste electrode (CPE) toward fluoroquinolones antibiotics ofloxacin (OFL) and ciprofloxacin (CIP), The drugs used to treat pneumonia caused by COVID-19. The synthesized Ca2CuO3 NS dramatically enhanced the anodic peak response of CPE toward both drugs compared to the unmodified one and other modified electrodes. The simultaneous detection of the two antibiotics was performed in the linear range of 0.09–1.0 μM for OFL and 0.05–0.8 μM for CIP with the LOD of 0.027 μM and 0.012 μM, respectively. The suggested method was applied successfully to determine OFL and CIP in real samples.